Historical development of Islamic integrated education in Malaysia since 15th century: current needs for the globalized world - Baba, Sidek; Salleh, Mohamad Johdi; Zayed, Tareq M; Harris, Ridwan (Centro Edizioni Universita Macerata, 2018)
Unlike traditional Islamic education (IE) systems, Islamic Integrated Education (IIE) emphasizes on developing graduate competency to generate employability to cope with an increasingly globalized world, while pursuing the core principles of IE. This paper tracks how IIE grew in Malaysia in the course of time and what are the opportunities offered for the students currently in primary, secondary and tertiary levels at IIE institutions. Historically, Islamic education in the Malay Archipelago (presently modern day Malaysia) started since Muslims ruled in Melaka around the 14th century. After the independence from British colonization, Malaysia retained the dualistic system of education i.e. separate Islamic and secular education systems. At current time, the Islamic education has been developed in an integrated way to accommodate the advancement of science and technology in Islamic subjects and thoughts. In this light, this paper presents the development of major aspects of IIE, such as pedagogy, curriculum, textbooks, teacher’s training and assessment through the different ages till the present, based on available resources. Finally, this paper suggests that the IIE still needs to be enhanced in terms of quality and quantity of the educational institutions and the teachers. In this regard, teachers must be adequately trained to be able to creatively integrate the teaching of the Muslim holy scripture, the Quran with science, and vice versa.